Chemical composition and antiparasitic activity of essential oils from leaves of Guatteria friesiana and Guatteria pogonopus (Annonaceae). Issue 2 (4th March 2017) - Meira, Cássio S.; Menezes, Leociley R. A.; dos Santos, Tatiana B.; Macedo, Taís S.; Fontes, José E. N.; Costa, Emmanoel V.; Pinheiro, Maria L. B.; da Silva, Thanany B.; Teixeira Guimarães, Elisalva; Soares, Milena B. P.
Abstract: Natural products represent a valuable source for discovery of antiparasitic agents. Here, we describe the antiparasitic activity from essential oils extracted from leaves of Guatteria friesiana (EOGF) and Guatteria pogonopus (EOGP) (Annonaceae). The essential oils were obtained by hydrodistillation and analyzed by GC/MS and GC-FID. The sesquiterpenes are more abundant in both essential oils. G. friesiana are dominated by β-eudesmol (51.9%), γ-eudesmol (18.9%) andα-eudesmol (12.6%). The major compounds identified for EOGP were spathulenol (24.8%), γ-amorphene (14.7%) and germacrene D (11.8%). The essential oils demonstrated potent trypanocidal and antimalarial activities with values of IC50 lower than 41.3 μg/mL . EOGF also inhibits the proliferation of amastigotes. In addition, we identified significant ultrastructural alterations induced by the essential oils, especially in the cell membrane, Golgi complex, endoplasmatic reticulum and mitochondria. The results presented herein reinforce the potential of other members of this family for search of antiparasitic compounds.